Tungsten disulfide Quantum Dots Based Disposable Paper Based Lab on GenoChip for Specific Meningitis DNA Detection. Issue 10 (28th May 2020) - Gupta, Riya; Ozhukil Valappil, Manila; Sakthivel, Arunkumar; Mathur, Ashish; Pundir, Chandra Shekhar; Murugavel, Kathiresan; Narang, Jagriti; Alwarappan, Subbiah
Abstract : Tungsten disulfide quantum dots (WS2 QDs) embedded lab on genochip based analytical device (PAD) was developed for the specific DNA detection of Meningitis, a life threatening disease. This paper-based lab on genochip was designed by grafting the two electrodes onto the surface of paper using conductive ink. The WS2 QDs were characterized by X-ray diffraction technique, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Following this, specific oligonucleotide sequence of DNA (capture probe) was immobilized over the surface of WS2 QDs/PAD electrode. The ssDNA/WS2 QDs/PAD device was characterized electrochemically by cyclic voltammetry. The device was employed for detection of target DNA (by hybridization) by employing methylene blue (MB) as an indicator. The biosensor exhibited a wide linear response in the range 1 nM–100 μM towards the target DNA. The limit of detection (LOD) of target DNA of the proposed device is 1 nM. The advantageous features of this device than the existing biosensors include cheaper analysis cost, tiny sample requirements and stability.